A Short Humoristic Text for the Training of Students with Specialized of Tourism - Mavlyuda Ibragimovna, Gadoeva; Fotima Saidovna, Vahidova; Nargisabegim Suleymanovna, Kobilova (International Journal of Psychosocial Rehabilitation, 2020)
This article is about formation of speech situations on the basis of short humoristic text to teaching students of the direction of training “tourism” to the English language. The main point of the article is the formation of the students’ oral speech in English. This article raised up the issue not only forming conversational skills of the students based on short humoristic texts but attitude towards foreign tourists as well as ethic manner of their communication with them. As a matter of fact, ESP combines subject matter and English language teaching. Such a combination is highly motivating because students are able to apply what they learn in their English classes to their main field of tourism study. In this article, we will talk about students studying in the field of Tourism for whom the act of communication in English will be motivated and necessary only if a professionally significant speech situation is created. For many professions in the field of tourism, knowledge of a foreign language is a professionally significant quality. Since many situations of professional communication require a high level of specialist preparedness for this type of activity: receiving a booking by phone from a foreign client by a travel agent; escort tourists from different countries throughout the trip by an employee of tour operator company; communication with foreign colleagues on issues of cooperation, exchange of experience, etc. Examples of comic stories taken from the popular American edition of Reader’s Digest. In the following joke, as we suppose, the potential is laid for creating a situation of communication in order to discuss the probabilistic development of events, i.e. students can recall the understatement of the story, finding out what could happen if the character behaved in a certain way. In addition, this joke touches upon an ethical problem, which consists in the fact that a personal opinion expressed aloud can offend another person or put him in an awkward situation.